2019
DOI: 10.1186/s13019-019-0965-0
|View full text |Cite
|
Sign up to set email alerts
|

Resection of a huge mediastinal well-differentiated liposarcoma involving left thoracic cavity

Abstract: Background Mediastinal lipoma/liposarcoma is a rare tumor of the mediastinum. Case presentation This article reported one case of giant anterior superior mediastinum well-differentiated liposarcoma involving the left thoracic cavity with symptom of dysphagia. The mediastinum liposarcoma was completely resected through a left thoracotomy. Histologic examination and molecular pathological test clarified the diagnosis as well-differentiated mediastinal liposarcoma. There h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It should be mentioned that only 8 historical WDLs (6.8%) were analyzed by FISH, including 6 MDM2-amplified cases, 1 case with equivocal MDM2-FISH results, and 1 CPMnonamplified case (10,12,20,(31)(32)(33)(34). In our study, all 18 tested WDLs were 12q13-15 amplified, including 17 MDM2amplified cases and 1 FRS2-amplified/MDM2-nonamplified/ CDK4-nonamplified tumor (case 4).…”
Section: Discussionmentioning
confidence: 77%
“…It should be mentioned that only 8 historical WDLs (6.8%) were analyzed by FISH, including 6 MDM2-amplified cases, 1 case with equivocal MDM2-FISH results, and 1 CPMnonamplified case (10,12,20,(31)(32)(33)(34). In our study, all 18 tested WDLs were 12q13-15 amplified, including 17 MDM2amplified cases and 1 FRS2-amplified/MDM2-nonamplified/ CDK4-nonamplified tumor (case 4).…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, Clamshell incisions are difficult to achieve sufficient exposure in this case. It has been reported that mediastinal liposarcoma was removed through a left thoracic incision ( 8 ), but the tumor invaded the superior vena cava and pericardium in this case, so this type of incision is not suitable for fully exposing the superior vena cava and pericardium. Median sternotomy is a common approach to resecting mediastinal tumors.…”
Section: Discussionmentioning
confidence: 85%
“…The amplification of these two genes is accepted as a diagnostic criterion for distinguishing well-differentiated liposarcoma from lipoma which can be a diagnostic pitfall, as our presented case has shown ( 1 , 6 , 16 ). Chemoresistance and low radiosensitivity of tumors arising from mesenchymal origin favor surgical approach as the only option for radical treatment ( 17 ). Surgical resection is therefore the most common treatment strategy for mediastinal liposarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although en bloc excision of the needle tract with the primary tumor can be performed, the evidence for improved oncologic outcomes is lacking ( 18 ). Previous case presentations have reported a variety of surgical approaches; however incision should be adopted to the location of the lesion ( 13 , 17 , 19 ). Median sternotomy represents a standard approach to anterior mediastinal tumors and can be extended to both sides in terms of hemiclamshell or clamshell incision and can be used for initiation of extracorporeal circulation if necessary ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation